KEMAMPUAN PENALARAN MATEMATIS SISWA PADA MATERI POLA BILANGAN MENGGUNAKAN PMRI - Nabila, Siti; Zulkardi, Zulkardi; Susanti, Ely (Universitas PGRI Sumatera Barat, 2023)
This study aims to describe students' mathematical reasoning abilities on number pattern material using PMRI. This type of research is descriptive qualitative research. This study consisted of three stages, namely the preparation stage, the implementation stage, and the data analysis stage. The research subjects were 3 class VIII students at SMP Negeri 9 Palembang. The data collection technique is a written test which consists of 2 description questions and interviews. The results of the written test which amounted to 2 description questions related to the number pattern material were used to see their abilities, while the interviews were used to clarify how the students' strategies were in answering the problems in the test questions. The data analysis technique is data reduction, data presentation, and drawing conclusions. Based on the research results, the indicators of mathematical reasoning ability that appear most often are making conjectures and finding patterns or characteristics of mathematical phenomena to make generalizations, while the indicators that rarely appear are drawing conclusions.